Sustaining transformative growth in Sri Lanka 2025-2030: Report of an Independent Growth Study Group under the auspices of ODI Global and the Centre for Poverty Analysis (CEPA) - Sirimal Abeyratne; Chandranath Amerasekera; Ravin Basnayake; Indrajit Coomaraswamy; Yvette Fernando; Dirk Willem te Velde; Esala Weerakoon; Shea Wickremasinghe; Ganeshan Wignaraja (ODI Europe, 2025)
Sri Lanka stands at a pivotal moment. After overcoming its most severe economic crisis since Independence, the country has shown remarkable signs of recovery and stabilisation. Yet, significant challenges remain - from persistent poverty to looming global uncertainties - threatening to stall progress unless urgent and bold reforms are enacted. This report, authored by an Independent Growth Study Group under the auspices of ODI Global and the Centre for Poverty Analysis (CEPA), outlines a crucial roadmap for sustainable and transformative growth for Sri Lanka from 2025 to 2030. It highlights the critical need for continued macroeconomic stability, strategic reforms and targeted support for key sectors such as tourism, digital innovation, manufacturing and agriculture. Prepared by a team of nine leading experts with extensive experience across public, private and international sectors, this study outlines six crucial policy areas that form the bedrock of a sustained growth plan: 1. Maintaining robust macroeconomic stability and enhancing credibility. 2. Deepening integration into global supply chains, boosting exports and attracting foreign direct investment. 3. Improving the efficiency and accessibility of factor markets. 4. Designing and implementing targeted policies for key sectors and markets. 5. Developing and strengthening policies to significantly reduce poverty. 6. Building strong political consensus and enhancing state capacity to effectively implement growth policies. The report provides detailed analysis and recommendations for each policy area, crucial for Sri Lanka's future prosperity.
Keywords: 330; Debt; Development finance; Economic transformation; Economic growth; Asia; Sri Lanka; Trade & investment